Guidelines for the follow‐up of patients undergoing bariatric surgery. Issue 3 (June 2016) - O'Kane, Mary; Parretti, Helen M; Hughes, Carly A; Sharma, Manisha; Woodcock, Sean; Puplampu, Tamara; Blakemore, Alexandra I; Clare, Kenneth; MacMillan, Iris; Joyce, Jacqueline; Sethi, Su; Barth, Julian H
Summary: Bariatric surgery can facilitate weight loss and improvement in medical comorbidities. It has a profound impact on nutrition, and patients need access to follow‐up and aftercare. NICE CG189 Obesity emphasized the importance of a minimum of 2 years follow‐up in the bariatric surgical service and recommended that following discharge from the surgical service, there should be annual monitoring as part of a shared care model of chronic disease management. NHS England Obesity Clinical Reference Group commissioned a multi‐professional subgroup, which included patient representatives, to develop bariatric surgery follow‐up guidelines. Terms of reference and scope were agreed upon. The group members took responsibility for different sections of the guidelines depending on their areas of expertise and experience. The quality of the evidence was rated and strength graded. Four different shared care models were proposed, taking into account the variation in access to bariatric surgical services and specialist teams across the country. The common features include annual review, ability for a GP to refer back to specialist centre, submission of follow‐up data to the national data base to NBSR. Clinical commissioning groups need to ensure that a shared care model is implemented as patient safety and long‐term follow‐up are important.